Correcting and verifying the copywriting of “Zad al-Ma’ad fi Mahamat Usul al-Iqidan” by Sheikh Marouf Nodhi - Ashkouh, Abdul Rahman; Aziz, L.Dr. Hamid Muhammad Amin (Sulaimani Journal for Humanities, 2024)
The poem "Zad al-Ma'ad fi Muhimmat Usul al-I'tiqad" (Provision for the Hereafter on the Essentials of the Foundations of Belief) is a work by Sheikh Ma'ruf al-Nawdahi in Persian on the science of Kalam (Islamic theology). It consists of 157 verses and contains a concise summary of the most important issues of Kalam. It remains a manuscript that has not been previously edited or published. However, fortunately, the researchers obtained two manuscripts and undertook its study and critical edition in this research. In the study section, after the introductory section, the researchers wrote about the life of Sheikh al-Nawdahi, followed by a brief history of Kalam in Islamic civilization. At the end of the study section, they discussed the importance of this poem among al-Nawdahi's works and his methodology in presenting matters of creed. In the critical edition section, they presented the edited text based on two manuscript copies and added annotations to some verses to clarify certain scholarly issues, provide biographical information on prominent figures, and document opinions and texts. Finally, they presented the most important findings of the research and the sources and references used. This research was undertaken with the aim of correcting a manuscript by a Kurdish scholar and to contribute to the revival of our ancestors' heritage. In this work, Noudi attempted to introduce Islamic beliefs to the general public in Persian. He followed the Ash'ari school of thought and drew upon the works of Sa'd al-Din al-Taftazani as much as possible.
Keywords: Theology; Sheikh Maruf alNawdhi; Scientific Systems; Ashari Theology